Answer:
y = 1/5x - 7/5
Step-by-step explanation:
y = 1/5x + b
-1 = 1/5(2) + b
-1 = 2/5 + b
-7/5 = b
Answer:
m=-3
Step-by-step explanation:
m=y2-y1/x2-x1
m=16-10/5-7
m=6/-2
m=-3
Answer:
Step-by-step explanation:
Like your other question, let's break it down systematically
6x + 9y - 9(6x - 3y + 8z)
Use the distributive property
6x + 9y - <u>9(6x - 3y + 8z)</u>
6x + 9y - 54x - 27y + 72z
Match like terms
6x - 54x = -48x
9y - 27y = -18y
72z - 48x - 18y
Answer:
he first is a numerical sentence and the second is an equation
Step-by-step explanation:
equation because there's "="
Answer:
4/16
Step-by-step explanation:
You ate 4 slice of the 16 slice pizza